THU0464 A genome-wide association study of gout in people of european ancestry. (15th June 2017) - Merriman, TR; Cadzow, M; Merriman, M; Phipps-Green, A; Topless, R; Abhishek, A; Andres, M; Bradbury, L; Buchanan, R; Cremin, K; Guzman, E de; Zoysa, J de; et al.
Abstract : Background: Gout progresses through three stages: hyperuricemia, deposition of monosodium urate (MSU) crystals, and innate immune system response to MSU crystals. Genome wide association studies (GWAS) have provided insight into the molecular control of progression to hyperuricemia. However, less is known about the progression from hyperuricemia to gout. Objectives: To conduct a GWAS for gout (where an immune response to MSU crystals has occurred) using 5, 835 cases - the largest GWAS of gout to date. Methods: The GWAS comprised 3 data sets: NZ/Eurogout (2, 365 clinically-ascertained cases; 1, 485 controls), the Health Professionals Follow-Up (HPFS) and Nurses' Health Studies (NHS) (1, 038 cases, self-ascertained using ACR criteria; 1, 095 controls), and UK Biobank (2, 432 cases, ascertained by self-report of gout, hospital records, and/or use of urate-lowering therapy; 102, 989 controls). The NZ/Eurogout samples were genotyped using the Illumina CoreExome v24 bead chip array (547, 644 markers), the HPFS/NHS samples using the Illumina OmniExpress v12 bead chip array (730, 525 markers), and the UK Biobank samples using an Affymetrix Axiom array (820, 967 markers). UK Biobank genotypes had been imputed to ∼73.3M SNPs. Neither the NZ/Eurogout nor NHS/HPFS genotype sets were imputed. Markers common to all three data sets (279, 939) were associated with gout (adjusted for sex, age) within each data set separately using PLINK 1.9. An inverse-variance weighted meta-analysis was done with meta v4.4 in R. Results: There were seven loci with genome-wide significant ( P <5x10 -8 ) evidence for association with gout: SLC2A9 (OR=1.67), ABCG2 (OR=1.72), GCKR (OR=1.24), SLC17A1-A4 (OR=1.20), SLC22A12 (OR=1.21), PDZK1 (OR=1.14), TRIM46 (OR=1.18). Conclusions: All seven loci have been previously associated with serum urate levels in GWAS. Our data emphasise the relative importance of genetic control of serum urate, compared to the genetic control of MSU crystal formation or the innate immune response, in determining gout. Disclosure of Interest: None declared